Insersi Nilai Karakter Melalui Pembelajaran Bahasa Arab: Character Value Insertion through Arabic Language Learning - Petta Solong, Najamuddin (ELOQUENCE : Journal of Foreign Language, 2023)
Background: Character values have not been specifically used as a self-development concept in Arabic language learning. Divinity, humanity, and nature-based character values should be inserted in all content and language skills. Purpose: The research is to interpret and provide an in-depth understanding of the concepts, methods, problems, and solutions in inserting character values through Arabic language learning from the perspective of Islamic education. Method: This research is literature research with a critical descriptive-analytical approach. Data sources were obtained from written documents in the form of reference books and articles. Data in the form of concepts is then analyzed descriptively with a content analysis approach. This approach is done by reconstructing concepts, describing ways, and providing solutions related to research problems. Results and Discussion: The results showed that the insertion of character values through Arabic language learning in the perspective of Islamic education has a dynamic concept and has a relationship between one material and another. The way of insertion can be done by inserting character education material into various learning components as a hidden curriculum. Combining Arabic language material with character values can essentially be a solution for teachers because the embryo of Islamic studies is essentially sourced from the Arabic-Islamic treasures that are imprinted on the concept of uswatun hasanah and tammimul akhlak. Conclusions and Implications: Contains one to two important sentences. This section provides a conclusion about the results of the research and what these results mean for us today, as well as the implications of the suggested research results for future research on the topic. The implication of this research is that teachers should always provide examples of behavior so that the insertion of character values in learning is more meaningful. In the aspect of learners, the content of Arabic language materials can be insinuated through their proficiency in speaking/good speech, listening/istima' good material, writing/kitabah good things and reading/qira'ah good content. The insertion of these four language skills can certainly shape the personality of learners who are more qualified, and weighty so that they become murabbi/murabbiyah who are oriented towards the pursuit of knowledge based not only on the level of sincerity but on the degree of pleasure of Allah and the Teacher.